Anticolonial form: Literary journals at the end of empire - Reza, Alexandra (New York, USA: Oxford University Press, 2024)
"Articulated anticolonialism: Literary journals and African decolonization addresses the relationship between culture and politics in two journals published in Europe by African writers: Presence Africaine, launched in Paris in 1947, and Mensagem, published between 1948 and 1964 in Lisbon. Grounded in extensive archival work, the book argues for a comparative and transnational approach to postcolonial literary studies, for the significance of the literary journal as a key form in the development of African writing in French, Portuguese, and English, and for a historically and geographically contingent understanding of the relationships between literature, culture and politics"--